Pengaruh Latihan Range Of Motion Terhadap Kekuatan Otot Pada Lansia Stroke Non Hemoragik Di Panti Sosial Tresna Werdha Budi Mulia 1 & 3 - Anisa Rafiana Deva; Aisyiah Aisyiah; Retno Widowati (Universitas Malahayati Lampung, 2022)
ABSTRACT One of the degenerative diseases in the elderly is stroke. Stroke is a neurological dysfunction that causes the death of brain cells so a lack of oxygen and nutrients in the blood causes bleeding around the brain. Stroke patients can experience an imbalance such as muscle weakness. One of the ways to increase muscle strength is to give Range of Motion exercises. The purpose of this research is to determine the muscle strength of stroke patients with non-hemorrhagic, before and after doing that range of motion exercises as well as to determine the effect of giving a range of motion exercises on muscle strength in non-hemorrhagic stroke elderly. The Quasi Experiment Design that using one group pre-post design method. Taking samples for this research is using the Total Sampling technique. All samples were given interventions such as the Range of Motion exercise which is done by taking all of ROM movements which aim to maintain or improve the ability to move joints and to increase muscle tone strength. The average muscle strength value before the intervention (pre-test) was 1.91. The average muscle strength value after the intervention (post-test) was 3.29. P-value (0.000) (0.05) that H0 is rejected and Hα is accepted, which means that there is an influence between the range of motion exercises on muscle strength in the elderly with non-hemorrhagic stroke. Range of motion exercises affects muscle strength in non-hemorrhagic stroke elderly. Keyword: Muscle strength, Elderly, Range of Motion, Stroke ABSTRAK Salah satu penyakit degeneratif pada lansia adalah stroke. Stroke adalah disfungsi neurologis yang menyebabkan sel otak menjadi mati sehingga kekurangan oksigen dan nutrisi dalam darah yang menyebakan perdarahan sekitar otak. Pasien stroke dapat mengalami ketidakseimbangan berupa kelemahan otot. Salah satu cara untuk meningkatkan kekuatan otot adalah diberikan latihan Range of Motion. Penelitian ini bertujuan untuk mengetahui kekuatan otot pasien stroke non hemoragik sebelum dan setelah dilakukan latihan range of motion serta untuk mengetahui pengaruh pemberian latihan range of motion terhadap kekuatan otot pada lansia stroke non hemoragik. Penelitian Quasy Eksperimen Design dengan menggunakan metode one group pre-post design. Pengambilan sampel pada penelitian ini menggunakan teknik Total Sampling. Seluruh sampel diberikan intervensi berupa latihan range of motion yang dilakukan dengan cara mengikuti gerakan ROM yang bertujuan untuk mempertahankan atau memperbaiki kemampuan menggerakan persendian dan untuk meningkatkan kekuatan masa otot tonus. Rata-rata nilai kekuatan otot sebelum intervensi (pre-test) adalah 1,91. Rata- rata nilai kekuatan otot sesudah intervensi (post-test) adalah 3,29. Nilai P value (0,000) (0,05) bahwa H0 ditolak dan Hα diterima yang artinya terdapat pengaruh antara latihan range of motion terhadap kekuatan otot pada lansia stroke non hemoragik. Latihan range of motion berpengaruh terhadap kekuatan otot pada lansia stroke non hemoragik. Kata Kunci : Kekuatan Otot; Lansia; Range of Motion; Stroke